An Analysis of Organisational, Operation and Individual Issues in Classroom Communication of Content Lecturers - Muhammad, Ahmad Mazli; Othman, Noor Ahnis; Rahmat, Noor Hanim (American Journal of Education and Learning, 2019)
In countries where English is not the main language of communication, teaching content courses in English is a challenge for lecturers. Past studies have shown that there are issues in the teaching of content subjects. Past studies have been done to investigate the challenges of teaching and learning content subjects in English. Some content lecturers may not face difficulty in understanding materials in English. However, when it comes to teaching the content subject in a language where the teachers are not familiar with, both teaching and learning become difficult. This quantitative pilot study is done to identify the needs amongst content lecturers in a tertiary setting. The instrument used is rooted from needs analysis model by McGehee and Thayer (1961) and challenges faced by content lecturers by Hung and Lan (2017). 30 lecturers participate in this study. Results of this study provide pedagogical implications in the teaching and learning of content subjects.